Laparoscopic management of persistent gastrocutaneous fistula after feeding gastrostomy appliance removal in children - Mohammad Gharieb Khirallah; Nasir Bustangi (Annals of Pediatric Surgery, 2020)
Abstract Background Feeding gastrostomy is widely used in children that have troubles of swallowing and need to stablish enteral feeding. There are several methods for creation of that stoma. After the children gain their normal ability of swallowing, this tube or appliance is removed. Failure of spontaneous closure of gastrostomy opening after removal of the tube was reported with an incidence of 0.5 to 3.9%. The purpose of authors was to study laparoscopic management of persistent gastrocutaneous fistula after failure of conservative measures. Results There were 19 patients, 12 males. Main cause for feeding gastrostomy was neurological. Most feeding gastrostomy tubes were inserted endoscopically. The mean operative time was 57 ± 10.2 min. The mean time of full oral intake was 24 ± 3.5 h. No wound infection had developed. There was no recurrence of fistula after management. Conclusion Laparoscopic management of persistent gastrocutaneous fistula is safe, feasible, and associated with no recurrence of fistula.